Examining Passages with Differing Equivalence in The Finnish Translation of Gregory Koukl’s Tactics - Karru, Sami (My University, 2025)
In this thesis, I examine and compare translated passages between Gregory Koukl’s book Tactics and its Finnish translation Taktinen viisaus. The equivalence of the examined passages differs from the general equivalence between the book and its translation. The book discusses Christian themes, meaning that the thesis belongs to the field of religious translation. The aim of the thesis is to establish how the translator has adapted the translation into the Finnish culture for the benefit of the Finnish readers. I have conducted this by reading the original book and the translation side by side, searching for passages that include adaptations made by the translator. Then I discuss 15 passages that demonstrate the adaptations. The analysis shows that the translator has mostly preferred a word-for-word translation style and refrained from making clear changes and adaptations to the text. He has made some adaptations when translating realia and in some other places where the changes have improved the text. The translation includes passages where no adaptations have been made even though it would have benefited the readers. The results of the thesis are only applicable to the translation in question, and it would be beneficial to conduct similar studies into the translations of other religious books in the future.
Keywords: Religious Translation, Equivalence, Comparison